2020
DOI: 10.1021/acssuschemeng.0c06480
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Water Harvesting System and Mechanical Performance from Janus Fibers with Polystyrene and Cellulose Acetate

Abstract: Water resources are shrinking year by year, and fog water collectors (FWCs) are already being used in humid regions, where populations have limited access to traditional water resources. The aim of this study was to use electrospun fibers as FWCs to collect water. Two polymers with different wetting and mechanical properties were successfully combined to create a Janus structure from hydrophobic polystyrene (PS) and hydrophilic cellulose acetate (CA). These fibers, with a specially designed gutter shape, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 79 publications
0
35
0
Order By: Relevance
“…However, the water transport from PS fibers was problematic due to high P f (60 ± 3%). Additionally, the PS mesh had much larger pore size of 67.59 ± 8.30 μm 2 , 59 which is three orders of magnitude higher than for PA11 mesh. The large spaces between the microfibers trap the water droplets for longer, slowing down the drainage, which decreases the water collection efficiency.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the water transport from PS fibers was problematic due to high P f (60 ± 3%). Additionally, the PS mesh had much larger pore size of 67.59 ± 8.30 μm 2 , 59 which is three orders of magnitude higher than for PA11 mesh. The large spaces between the microfibers trap the water droplets for longer, slowing down the drainage, which decreases the water collection efficiency.…”
Section: Resultsmentioning
confidence: 91%
“…The water collection rate obtained for PA6 is similar to results from a previous study for hydrophilic cellulose acetate fibrous meshes with average fiber diameter of 0.54 ± 0.16 μm, which reached 45 mg cm −2 h −1 . 59 Also, the water collection rate for hydrophobic polystyrene (PS) microfibers with average diameter of 4.80 ± 0.22 μm achieved 59 mg cm −2 h −1 , 59 which is comparable to PA11. However, the water transport from PS fibers was problematic due to high P f (60 ± 3%).…”
Section: Resultsmentioning
confidence: 92%
“…Tong et al 40 and Huang et al 67 reinforced PVA with different contents of CNTs and found an increase of the tensile modulus, tensile strength, and elongation‐to‐break. In turn, Knapczyk‐Korczak et al 68 found that the addition of CA to polystyrene led to a more durable and mechanically stable material. Also, Kurokawa et al 69 observed that the mechanical properties of polylactic acid were improved by CA addition.…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] A fiber mesh based on textile weaving technology, called Raschel mesh, has been widely used in arid regions due to the low cost and simple fabrication, however, the single function greatly affects its fog harvesting efficiency. [27] Currently, a great deal of highly effective fog harvesting methods based on optimizing the physical structure of the fog harvesting devices (FHDs) has been reported, such as kirigami cutting, [28] electrospinning, [29] 3D printing, etc. [30,31] In addition, inspired by the unique wettability of the Namib desert beetle, much attention has been paid on the surface wettability modification, including spray coating, [32] selective grafting, [33] photomask, etc.…”
Section: Introductionmentioning
confidence: 99%